Female tabagism associated mastitis: a case report related to low quality cigarettes consumption in Magé, Rio de Janeiro (Research, Society and Development, 2022)
Objective: to report a case of periductal mastitis, whose initial presentation has been necrosis of nipple in a client of the Public Unified Health System (SUS) in the city of Magé / Rio de Janeiro. The public healthcare system client had reported prolonged use of cheap cigarettes which she used to smoke and which she could afford. Method: case report qualitative study, anchored in anamnesis and physical examination with emphasis on patient social history and pathophisiology of benign breast mastitis related to tobacco use. Result: According to anamnesis and physical examination, it is suggested that a chronic inflammatory process in breast ducts had occurred. A chronic breast inflammatory process may be linked with toxins eliminated in cigarette combustion, nevertheless an overwhelming patient social vulnerability and issues concerning self-care must be regarded by primary health care nursery. Conclusion: Quitting smoking may imply multifactorial aspects, including willpower, psychiatric and somatic disorders, poverty and little access to healthcare system in Brazil. Body care should have been emphasized concerning medical and nursing management. In Magé, mastitis diagnosis associated with tobacco use has been somewhat frequent, and recurrent non-puerperal breast abscess complicates most cases. Often, poor female patients with low self steem have consumed cheaper cigarettes, perhaps less subject to appropriate quality control.